Analisa Nilai Parameter untuk Memprediksi Hasil Panen Padi di Jawa Timur pada Periode 2020 – 2024 - Faisal, Faisal; Primadani, Joshua; Bumbung, Bumbung; Abna, Fabio Bintang Azriel; Zuma , Adhriana; Sigalingging, Rosian Oktavia; Misrianto, Misrianto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study analyzes the parameter values ​​to predict rice yields in East Java in the period 2020-2024. By using classical and modern methods such as Single Exponential Smoothing (SES) and Double Exponential Smoothing (DES) optimized through the Golden Section method, this study aims to determine the best parameters to improve the accuracy of crop yield predictions. The data used were taken from the Central Bureau of Statistics of Indonesia, and the analysis shows that the DES method is more optimal than SES, with a smaller Mean Absolute Percentage Error (MAPE) value. The results of the study are expected to contribute to more effective agricultural sector planning in East Java.